2018
DOI: 10.2991/jrnal.2018.5.3.7
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Lumbar Burden Evaluation of Work using One Smartphone

Abstract: Smartphone lumbar burden gyro sensor state estimation acceleration sensor JACK A B S T R A C TIn this paper, we propose the human lumbar burden evaluation method and state estimation system using a smartphone and an application on agricultural work. The proposed system consists of two functions: (1) "State estimation" has a function of estimating posture (Stand up, Sit down, Crouch, Walk, etc.,) of the subjects, (2) "Lumbar burden estimation" has a function to estimate the angle of the waist from the angle of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The Japanese Ministry of Health, Labour and Welfare's "Guidelines for Prevention of Back Pain in the Workplace" recommends the knee-bend lifting method. The results of the previous study and the analysis using the "Yo-bukun" application for measuring back strain showed that the lifting method with the knees bent reduced the amount of back strain compared to the lifting method without knees bent [1], [2], [3]. In addition, the previous study showed that the lifting method with the knees bent was associated with a lower EMG burden when the lifting object was located close to the body's center of gravity [4], [5].…”
Section: Introductionmentioning
confidence: 97%
“…The Japanese Ministry of Health, Labour and Welfare's "Guidelines for Prevention of Back Pain in the Workplace" recommends the knee-bend lifting method. The results of the previous study and the analysis using the "Yo-bukun" application for measuring back strain showed that the lifting method with the knees bent reduced the amount of back strain compared to the lifting method without knees bent [1], [2], [3]. In addition, the previous study showed that the lifting method with the knees bent was associated with a lower EMG burden when the lifting object was located close to the body's center of gravity [4], [5].…”
Section: Introductionmentioning
confidence: 97%
“…The Yo-bukun application [6], [7], a collaborative effort between the Faculty of Engineering at Miyazaki University and Densan Corporation in 2022, is an iPhone application quantifying and displaying lower back burden. This application is calibrated when the user stands upright, and calculates the amount of lumbar burden based on the tilt of the iPhone.…”
Section: Introductionmentioning
confidence: 99%
“…The smartphone application called Yo-bukun allows you to estimate the lumbar burden when holding an object in real time by placing a smartphone in the chest pocket [1], [2]. The estimation method of the Yo-bukun involves utilizing smartphone sensors such as the acceleration sensor and gyro sensor to assess the user's state (standing, sitting, turning, crouching, walking).…”
Section: Introductionmentioning
confidence: 99%